Acrylonitrile-grafted recycled papers for Ni(II) ions removal. (2021) - Awang, N.A.; Salleh, W.N.W.; Ahmad, S.Z.N.; Ismail, N.H.; Rosman, N.; Sazali, N.; Ibrahim, H.; Ismail, A.F.
Abstract: Recently, naturally occurring biopolymers have gained interests in its application as adsorbent for the removal of metal ions. The graft copolymerization modification of acrylonitrile monomer in the presence of ceric ammonium nitrate was successfully done on extracted recycled papers. The fabricated grafted adsorbent was analyzed by using scanning electron microscopy (SEM) with energy dispersive X-ray (EDX) mapping, X-ray powder diffraction (XRD), as well as Fourier-transform infrared spectroscopy (FTIR). The parameters of the adsorption process were varied for the pH of the solution, concentration of Ni(II) ions, and time duration. As a result, the most optimum condition was achieved at pH 5 with 160 mg/L in a duration of 1 h, which reached 317.5 mg/g equivalent to 79.3% removal. The adsorption behavior tallied with Freundlich and Pseudo-second-order for adsorption and kinetic models, respectively. Convincingly, acrylonitrile-grafted recycled papers are able to be competitive and act as an efficient adsorbent in metal ions removal.